ONCOLOGY REHABILITATION - AN ALTERNATIVE TO BREAST CANCER TREATMENT - Yani Shivachev; Stanislava Bogomilova; Gergana Nenova; Valentin Velchev (Peytchinski Publishing, 2020)
Introduction: Worldwide breast cancer is the most common malignancy disease with a frequency of more than 6 million. The treatment consists of surgical intervention, chemotherapy, radiation, and often follow-up medical care in the long-term treatment is neglected. As a result of a partial or total mastectomy, one of the complications that patients develop is lymphedema, which may occur months or years after the surgery. This necessitates the search for systematic and effective approaches for these patients in order to improve physical and mental well-being, resocialization and return to previous levels of activity in daily life. Case report: In 2019 a 58-year-old female patient, visited Medical University of Varna and University center of East medicine with the following complaints: pain in the armpit area, lymphedema of a right upper limb, a sense of weight and motor deficiency in the hand. In 2017 she is diagnosed with breast cancer by conducting an operative intervention consisting of a partial mastectomy with removal of 12 lymph nodes, followed by chemotherapy, radiotherapy treatment and medication therapy. For 2 years, the patient seeks help from a variety of healthcare professionals whose methods lead to short and unsatisfactory results. Impaired quality of life in daily activities is the main reason the patient to refer to the specialists at the University center of East medicine, offering a different and complex approach aimed at the patient's overall recovery. Conclusion: Early diagnosis and subsequent successful treatment approach are the path to holistic, systematic and effective treatment in cancer patients.